(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2016)
During the reign of Minh Mang (1820-1841) in Vietnam, court officials were sent to the Malay Archipelago as envoys to strengthen diplomatic relationships and gather information on all the countries visited by the envoys. The main countries in the Malay Archipelago visited by the court envoys included Ma-la-kha [Malacca], Giang-luu-la [Batavia, Jakarta], Tan-gia-ba [Singapore], Tan-lang-du [Penang], and La-tong [Luzon]. These diplomatic missions were accomplished by several significant court officials including Ly Van Phuc. This paper attempts to explore the records from his visits and observations on political and socioeconomic aspects of the Malay Archipelago, especially on Malacca, Penang and Singapore. This research is significant as it recaptures valuable depictions of the region through a Vietnamese perspective. Keywords: Vietnam, Malay Archipelago, Ly Van Phuc, The Straits Settlements